2018
DOI: 10.1002/jsfa.9236
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inclusion of mushroom (Flammulina velutipes) stem waste on growth performance and immune responses in growing layer hens

Abstract: FVW at the 6% level can be used as a potential phytogenic feed stuff in growing layer hen rations with respect to improving the immune response without affecting normal weight gain. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
(70 reference statements)
4
19
0
Order By: Relevance
“…and other cytokines to stimulate humoral immunity [57]. INF-γ and IL-2 are mainly expressed by Th1 cells, while IL-4 is mainly expressed by Th2 cells, which play important roles in mediating cellular and humoral immune responses, respectively [58].…”
Section: Effects Of Tp On Genes Expression Of Immune-related In the Smentioning
confidence: 99%
“…and other cytokines to stimulate humoral immunity [57]. INF-γ and IL-2 are mainly expressed by Th1 cells, while IL-4 is mainly expressed by Th2 cells, which play important roles in mediating cellular and humoral immune responses, respectively [58].…”
Section: Effects Of Tp On Genes Expression Of Immune-related In the Smentioning
confidence: 99%
“…On the other hand, antibiotic has been used for few years with a view to enhance growth performance and health status in broilers ( Mahfuz et al., 2019 ). But overapplication of antibiotics in food animal production has created health hazards ( Mahfuz et al., 2018a ). Currently, the European Union, the United States, and other developed countries have prohibited the application of in-feed antibiotics ( Li et al., 2019 ; Long et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the antibody titers against infectious bursal diseases virus were greater in mushroom Ganoderma lucidum fed groups than the control diets, in pullet [55]. In another study by Mahfuz et al [66] antibody response on ND was greater (p < 0.05) in the 6% mushroom stem fed group and IB were greater (p < 0.05) in all levels of mushroom fed groups than both the positive and negative control diets, in laying hens. This study further demonstrated that the serum cytokines concentrations (IL-2, IL-6, IL-4, and TNF-α) were higher (p < 0.05) in mushroom feed groups than the control and antibiotic fed groups, in laying hens.…”
Section: Application Of Medicinal Mushrooms On Health Status In Layermentioning
confidence: 84%